Knowledge and Its Association with Nutritional Status of Students Receiving the Makan Bergizi Gratis (MBG) Program in Surabaya and Sidoarjo - Triska Susila Nindya; Trias Mahmudiono; Sasha Anggita Ramadhan; Azizah Ajeng Pratiwi; Mahmud Aditya Rifqi; Diah Indriani; Andriyanto Andriyanto; Elya Sugiyanti (Universitas Airlangga, 2026)
Background: The triple burden of malnutrition remains a significant public health issue among school-aged children in Indonesia. In response, the Makan Bergizi Gratis (MBG) Program was introduced to improve adolescents’ nutritional intake. Objectives: This study aimed to assess the nutritional status and level of nutrition knowledge among junior high school students participating in the MBG Program in Surabaya and Sidoarjo, Indonesia. It also examined the relationship between nutritional knowledge and nutritional status. Methods: A cross-sectional study was conducted among 650 junior high school students participating in the Makan Bergizi Gratis (MBG) Program in Surabaya and Sidoarjo. Data on individual characteristics and nutritional knowledge were collected using a self-administered structured questionnaire. Nutritional status was determined using body mass index-for-age based on World Health Organization (WHO) growth reference standards, while nutritional knowledge was categorized using percentile cut-off points. The relationship between nutritional knowledge and nutritional status was analyzed using the Pearson Chi-square test. Results: Most students exhibited normal nutritional status (67.8%), although instances of undernutrition (7.1%) and overnutrition (25.1%) persisted. Regarding nutrition knowledge, nearly half were classified as moderate (47.4%), followed by low (35.4%) and high (17.2%) knowledge. Students demonstrated a solid grasp of balanced nutrition and the importance of breakfast, with over 90% correctly answering several key questions. Correct responses decreased for Isi Piringku portion guidelines (46.3%) and handwashing practices (59.4%). Nutrition knowledge was significantly associated with nutritional status (Pearson’s chi-square test, p=0.037). Conclusion: Most junior high school students receiving the MBG Program demonstrated normal nutritional status and moderate nutrition knowledge levels, although undernutrition and overnutrition persisted in some cases. A significant association was found between nutritional knowledge and nutritional status, highlighting the potential value of incorporating structured nutrition education into the MBG Program.